Cultural netizenship : social media, popular culture, and performance in Nigeria - Yeku, James (Indiana University Press, 2022)
How does social media activism in Nigeria intersect with online popular forms--from GIFs to memes to videos--and become shaped by the repressive postcolonial state that propels resistance to dominant articulations of power? James Yékú proposes the concept of "cultural netizenship"--internet citizenship and its aesthetico-cultural dimensions--as a way of being on the social web and articulating counter-hegemonic self-presentations through viral popular images. Yékú explores the cultural politics of protest selfies, Nollywood-derived memes and GIFs, hashtags, and political cartoons as visual texts for postcolonial studies, and he examines how digital subjects in Nigeria, a nation with one of the most vibrant digital spheres in Africa, deconstruct state power through performed popular culture on social media. As a rubric for the new digital genres of popular and visual expressions on social media, cultural netizenship indexes the digital everyday through the affordances of the participatory web. A fascinating look at the intersection of social media and popular culture performance, Cultural Netizenship reveals the logic of remediation that is central to both the internet's remix culture and the generative materialism of African popular arts.